Follicle cell processes: a shark thing?. Issue 3 (25th October 2016) - Dunbar, M.; Onuora, C.; Morgan, S.; Stone, F. E.; Huckaba, T. M.; Davenport, I. R.
Abstract : Follicle cell processes (FCP) are identified in two species of carcharhinid shark (Selachii) but are absent in the little skate Leucoraja erinacea (Batoidea). This suggests that FCPs are either a unique structure that evolved in selachians or were lost by the batoids after their divergence, some 280 mya . The presence of FCPs in the selachians would be consistent with the evolution of large oocytes in this group of animals.